Physical activity and sedentary behaviour in Czech adults: results from the GPAQ study - Hamrik, Zdenek; Sigmundová, Dagmar; Kalman, Michal; Pavelka, Jan; Sigmund, Erik (European journal of sport science, 2014)
The levels of physical activity (PA) and sedentary behaviour are significant indicators of health behaviour and their monitoring is crucial in developing public policy in the area of health promotion and non-communicable disease prevention. The aim of the study was to describe the prevalence of PA and sedentary behaviour as well as age and gender differences in Czech adults (18-90 years old, N = 1753; 48.4% male) participating in the Global Physical Activity Questionnaire (GPAQ) cross-sectional study 2011. To assess the significant differences between self-reported PA and sedentary behaviour the MANOVA, a post hoc Fischer's least significant difference (LSD) test and logistic regression were used. The level of PA was classified according to the amount of MET-minutes per week as high, moderate or low. Irrespective of age and gender, 32.3% of adults reported a low level of PA; 21.3% of adults fell within the category of moderate level of PA and 46.4% of adults reported a high level of PA. The level of PA decreases with age; men are generally more physically active than women. More than 60% of adults across all age categories are assessed as 'sedentary'. The highest rate of sedentary behaviour was observed in adults over 65 years of age. The development of national strategies for PA promotion together with the development and verification of specific intervention programmes, especially for women, should be a priority in the Czech Republic.
Keywords: dospělí; logistické modely; Sedentary Behavior; průzkumy a dotazníky; Female; Prevalence; Adult; sedavý životní styl; ženské pohlaví; průřezové studie; mladý dospělý; Logistic Models; Surveys and Questionnaires; Adolescent; pohybová aktivita; lidé; cvičení; Aged, 80 and over; Humans; Sex Factors; prevalence; zdravé chování; Age Distribution; Cross-Sectional Studies; Male; Aged; sexuální faktory; Czech Republic; Young Adult; věkové rozložení; Česká republika; Motor Activity; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Exercise; Middle Aged; mladiství; Health Behavior